Angel of hope - McDaniel, Lurlene (New York : Bantam Books, 2000)
After her older sister, Heather, enthusiastic about changing the world, returns from doing medical missionary work in Uganda, seventeen-year-old Amber, who feels confused about her future, decides to go to Africa on the next trip.
Companion to Angel of Mercy.
640
Accelerated Reader AR
Keywords: Sisters -- Fiction; Missionaries -- Fiction; Christian life -- Fiction; Uganda -- Fiction